2005
DOI: 10.1123/ijsnem.15.6.680
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Purified Oxygenated Water on Exercise Performance during Acute Hypoxic Exposure

Abstract: The purpose of this study was to assess the effects of purified oxygenated water on exercise performance under hypoxic conditions. Nine recreational male cyclists (age = 26.6 +/- 5.2 y, weight = 87.6 +/- 19.5 kg, VO2peak = 46.5 +/- 5.9 mL x kg(-1) x min(-1)) completed two 600 kJ cycling time trials under hypoxic conditions (FIO2 = 13.6% O2, Pbar = 641 mmHg) separated by 2 wk. Trials were completed following 3 d ingestion of 35 mL x kg(-1) x d(-1) of control (CON) or experimental (EXP) water. Time to completion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
2
13
0
1
Order By: Relevance
“…Despite anecdotal reports from athletes, few controlled studies have been conducted and therefore the ergogenic effects of these drinks remains questionable [5]. Of the limited studies which have examined the effects of oxygenated water, most have reported no effect on aerobic performance [610]. The majority of these studies have used VO 2 either at sub-maximal or maximal intensity as a measure of aerobic performance [6–9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite anecdotal reports from athletes, few controlled studies have been conducted and therefore the ergogenic effects of these drinks remains questionable [5]. Of the limited studies which have examined the effects of oxygenated water, most have reported no effect on aerobic performance [610]. The majority of these studies have used VO 2 either at sub-maximal or maximal intensity as a measure of aerobic performance [6–9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, no study has verified if the human gastro-intestinal tract has the potential to absorb O 2 into the hepatic portal vein. Previous human studies have used pulse oximetry [5, 10, 14] or blood gas analysis [6, 8] to quantify systemic O 2 concentrations with most reporting no change in oxygen saturation. However, muscle tissue O 2 saturation has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…5 Finally, a study of nine male recreational cyclists showed that oxygenated water did not improve performance even in mild acute hypoxia (P bar = 641 mm Hg). 7 These studies all meet the physiological expectation that oxygenated water would not improve incremental exercise to VO 2 MAX or recovery from strenuous exercise.…”
mentioning
confidence: 58%
“…Three controlled studies on oxygenated water and performance say not. [5][6][7] Willmert et al 6 measured resting, submaximal, and maximal VO 2 , circulatory variables, and blood lactate in 12 subjects who randomly consumed 500 ml of either oxygenated or plain bottled water. No differences were detected between conditions for any variable at rest or in exercise.…”
mentioning
confidence: 99%
“…Indeed, when the oxygen content of the products used in some studies was measured, it was found to be higher than tap water but failed to meet the oxygenation levels claimed by the manufacturers 15 16. Finally, a 3-day protocol of supplementation failed to achieve benefits to cycling time trial performance undertaken under hypoxic conditions 19. The importance of oxygen delivery to the muscles in determining the performance of many sports is clearly recognised.…”
Section: Introductory Remarksmentioning
confidence: 99%